FREQUENCY OF MPL AND JAK2 EXON12 GENE MUTATION IN MYELOPROLIFERATIVE NEOPLASMS - Latif, Sana; Khan, Saleem Ahmed; Mahmood, Asad; Mahmood, Rafia (Pakistan Armed Forces Medical Journal, 2020)
Objective: Detection of MPL and JAK2 exon12 gene mutation in myeloproliferative neoplasms (MPN) in JAK2V617F negative Myeloproliferative Neoplasms. Study Design: Cross sectional study. Place and Duration of Study: Department of Haematology, Armed Forces Institute of Pathology, from Jun 2017 to Jun 2018. Methodology: Total of 90 newly diagnosed JAK2V617F negative myeloproliferative neoplasms patients were enrolled in the study. Clinico-haematologic features were noted. DNA was extracted from bone marrow samples. Molecular analysis was performed for MPL and JAk2 exon 12 gene by Sanger Sequencing. Results were analyzed by using Genetic Analyzer HITACHI 3130. Results: Out of these 106 patients 86 were males and 20 were females. On mutation analysis of 16 (15%) patients were found positive for JAK2V617F while 90 (84.9%) were JAK2V617F negative. We then studied these 90 JAK2V617F negative myeloproliferative neoplasms patients for other mutations such as MPL gene and JAK2 exon12. On the basis of clinical features, physical examination, Blood complete picture, bone marrow aspiration and trephine biopsy findings 48 (53.3%) were diagnosed as PV, 22 (24.4%) as ET, 20 (22.2%) as PMF. JAK2 exon12 mutation analysis was screened in 48 (54%) patients and remaining 42 (46%) patients, out of which 22 (24.4%) ET patients and 20 (22.2%) were diagnosed as PMF analyzed for MPL gene mutations. Conclusion: We have found that none of these patients carry JAK2 exon12 and MPL gene mutation.